A new approach to model development of water distribution networks with high leakage and burst rates. (2015) - Latchoomun, L.; Ah King, R.T.F.; Busawon, K.
Abstract: Modelling real distribution networks can be particularly difficult if they are so leaky that the types of leak and their nature can hardly be determined from scarce field measurements. In this context, a new approach to model development of such WDNs is proposed. The method is based on leakage estimation from MNF and the burst frequency of AZPs. After applying it to a real DMA in Mauritius, the resulting calibrated model from EPANET is found to approach the actual status of the network very closely in terms of overall real losses, coefficients of discharge, nodal flow and pressure.